The theory of the individual in economics : identity and value - Davis, John Bryan (Advances in social economics., 2003)
The concept of the individual and his/her motivations is a bedrock of philosophy. Economics, though, is guilty of taking this hugely important concept without questioning how we theorise it. This superb book remedies this oversight.